The Prophet Shaving: Persians and the Origin of the Malay Hikayat Nabi Bercukur - Daneshgar, Majid (Der Islam, 2021)
This article is about a well-known anonymous folk story in the Malay-Indonesian world, called Hikayat Nabi Bercukur ("The Story of Prophet Shaving"), found in various different languages across the region. The only scholarly conjecture about its origin is based on the copy of a Malay manuscript held in Leiden which has been deliberately blackened and struck through by a reader who stated in the margin that the story is written by a Rāfiḍī and should not be believed. Although earlier scholars mentioned the title or the synopsis of this story in their works and bibliographical catalogues, the question "what is the origin of this story?" remained unanswered. In order to follow up on previous studies and to find an answer, this essay examines numerous original manuscripts and texts in various languages and provides a comparison between the Malay versions and their prototype. Also, to the best of my knowledge, the first edition and English translation of the prototype are presented.